A challenging Heck reaction of maleimides1. Issue 7 (9th July 2015) - Lim, Li Hui; Zhou, Jianrong (Steve)
<x xml:space="preserve">Abstract</x> A difficult Heck reaction of base-sensitive maleimides is realized by using a weak base in a carbonate solvent.